Apologizing with Threats? An Ethnocyberpragmatic Study of Social Commerce Content among the Madurese Ethnic Group - Putikadyanto, Agus Purnomo Ahmad; Suhartono, Suhartono; Mintowati, Mintowati; Cahyanto, Bagus; Setyawan, Agung (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Conventionally, apologies are understood as expressions of regret or corrective exchanges aimed at maintaining social order when a norm is violated. However, in the context of social commerce content among the Madurese ethnic group, apologies do not always signify remorse. This study examines the phenomenon of apologies accompanied by threats in the practice of Madurese social commerce on digital platforms such as Facebook and YouTube. The threats accompanying apologies can be either non-conditional or conditional, and are used to strengthen bargaining positions or assert the speaker’s authority. Using an ethnocyberpragmatic approach, this research highlights how apology utterances accompanied by threats or warnings are employed within Madurese social commerce content. Data were collected from social media posts showcasing bargaining interactions between sellers and buyers. The analysis reveals that apologies in this discourse do not function literally, but rather as part of a culturally distinctive trading strategy. In conclusion, social commerce within the Madurese community serves not only as a medium for economic transactions but also as a site for cultural expression and identity negotiation that remains vibrant in contemporary digital communication practices.